Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/art.23076
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of galectin 9 on rheumatoid arthritis by induction of apoptosis of synovial fibroblasts

Abstract: Objective. To compare the expression of galectin 9 (Gal-9) in synovial tissue (ST) from rheumatoid arthritis (RA) patients and osteoarthritis (OA) patients and to evaluate the effects of Gal-9 on fibroblast-like synoviocytes (FLS) in these patients.Methods. The expression of Gal-9 in ST and FLS was compared using immunohistochemical techniques. Apoptotic cells in RA and OA ST samples were detected by TUNEL assay. Apoptosis of FLS was analyzed by the sub-G 1 method in vitro. The in vivo suppressive effects of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 41 publications
(67 reference statements)
5
95
1
1
Order By: Relevance
“…Indeed, disruption of this mechanism using TIM-3 or galectin-9 blocking Abs has been reported to result in increased neutrophil infiltration and tissue damage in a model of liver ischemia/reperfusion (31), experimental adhesion formation (30), and multiple sclerosis (32). Conversely, administration of proteolytically stable recombinant galectin-9 ameliorated symptoms in a model of arthritis (34,35,66), diabetes (67), and multiple sclerosis (32). Galectin-9 has also shown to exhibit a protective effect in lung infection in a mouse model of hypersensitivity pneumonitis induced by Trichosporon asahii (41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, disruption of this mechanism using TIM-3 or galectin-9 blocking Abs has been reported to result in increased neutrophil infiltration and tissue damage in a model of liver ischemia/reperfusion (31), experimental adhesion formation (30), and multiple sclerosis (32). Conversely, administration of proteolytically stable recombinant galectin-9 ameliorated symptoms in a model of arthritis (34,35,66), diabetes (67), and multiple sclerosis (32). Galectin-9 has also shown to exhibit a protective effect in lung infection in a mouse model of hypersensitivity pneumonitis induced by Trichosporon asahii (41).…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytically stable human galectin-9 was a kind gift from GalPharma (Kagawa, Japan). Expression and purification of stable human galectin-9 was performed as previously described (34,35). In brief, galectins were expressed using the pET expression system (Novagen, Madison, WI) in Escherichia coli BL21 (DE3) and purified with a lactose-agarose column (Seikagaku Kogyo, Tokyo, Japan) and dialyzed against PBS.…”
Section: Abs and Recombinant Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gal-9 concentrations in the plasma and culture supernatants were measured using ELISA, as previously described with slight modification (Seki et al 2007;Katoh et al 2010). Briefly, 96-well plates (Nunc, Rockild, Denmark) were coated with an anti-human Gal-9 monoclonal antibody (clone 9S2-3; GalPharma, Takamatsu, Japan), and then samples were incubated for 1 hour at 37°C after blocking.…”
Section: Galectin-9 Measurementsmentioning
confidence: 99%
“…TIM-3 expression could be increased in healthy T-cells, but not in RA-derived T-cells, by treating the cells with the TIM-3 ligand, galectin-9 [76]. These results have even greater significance in view of previous findings which showed that a stable form of galectin-9, resistant to proteolysis unlike the other galectin isoforms, galactin-1, galactin-3, and galactin-8 stimulated RAFLS apoptosis and suppressed proliferation in vitro [77]. Thus, galectin-9-mediated CD4 + cell apoptosis appears to be deficient in RA.…”
Section: Bh3-only Proteinsmentioning
confidence: 57%